FIQIH SEKSUALITAS: MENGASAH KEARIFAN HUKUM ISLAM MELALUI MAQASHID SYARI’AH DALAM PROBLEMATIKA VAGINISMUS - Ahmad Muhtadi Anshor (Fakultas Agama Islam Universitas Wiralodra, 2021)
This study aims to formulate the jurisprudence of sexuality based on maqashid shari'ah in responding to the vaginismus problems experienced by women. This is because so far vaginism is a phenomenon that often occurs in women's lives and has not received a response in the aspect of Islamic law. Ignorance of Islamic law seems to give stigma and discrimination when women are faced with suffering from vaginismus. Whereas in the current contemporary era, maqashid shari'ah has a very strong position in formulating Islamic legal products based on humanity and justice. The study, which is based on this literature review, seeks to dialogue and re-actualize maqashid shari'ah as an effort to build Islamic law based on humanity and justice. Through a comprehensive study, this study finds that it is necessary to build Islamic jurisprudence based on maqashid shari'ah to respond to various problems related to the realm of sexuality. In actualization, vaginismus is a necessity that cannot be denied and can only be treated. So that the legal consequences that accompany it must have dimensions of humanity and justice.